(untitled) (Politeja, 2019)
The Main Categories of Richard Hooker’s Political Thought This article outlines the main philosophical and political issues of this late-Tudor Anglican divine. Hooker’s ideas, developed in Of the Laws of Eccclesiastical Polity, provide some atypical answers to typical questions about the state and itsconnection with the church. The first issue presented is the nature of law and reason: Hooker’s approach bears a strong resemblance to St. Thomas Aquinas’ thought here. We can also observe the naissance of a theory of a “social contract”, as society enters an agreement to nominate a governor over them. Hooker seems to be applying this theory to both the origins of the state and of the church. Indescribing the role of tradition in law-making, Hooker can be called the pioneer of the Conservative doctrine. We shall indicate the role of the Revelation in Hooker’s outlook and his polemics with the Puritans here. Finally, we will come to Hooker’s criticism of the theory of two powers, his favour of monism and its historical proponents, and to his arguments for the royal supremacy in England.